2017
DOI: 10.1088/1748-3190/aa8447
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wing flexibility on sound generation of flapping wings

Abstract: In this study, the unsteady flow and acoustic characteristics of a three-dimensional (3D) flapping wing model of a Tibicen linnei cicada in forward-flight are numerically investigated. A single cicada wing is modelled as a membrane with a prescribed motion reconstructed from high-speed videos of a live insect. The numerical solution takes a hydrodynamic/acoustic splitting approach: the flow field is solved with an incompressible Navier-Stokes flow solver based on an immersed boundary method, and the acoustic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…We believe that the application of this method to the current case of flapping wing flight is appropriate because it falls under the category of low-Mach flows and the Reynolds number is comparable to the validated cases. Our previous study [20] also showed that the directivity of the computed sound from the flapping wings was comparable to experimental measurements [17].…”
Section: ∇•supporting
confidence: 72%
See 2 more Smart Citations
“…We believe that the application of this method to the current case of flapping wing flight is appropriate because it falls under the category of low-Mach flows and the Reynolds number is comparable to the validated cases. Our previous study [20] also showed that the directivity of the computed sound from the flapping wings was comparable to experimental measurements [17].…”
Section: ∇•supporting
confidence: 72%
“…Previous experimental [17] and simulation works [18,19] on the sound production of flapping wings generally found that the flapping tone is directional and changes with flight conditions. Geng et al [20] showed that the flapping tone is mainly generated by the fluctuating aerodynamic forces. The sound signal and the force signal were related in both radiation pattern and amplitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a foil stroke, positive pressure is formed on the loading face due to fluid being displaced and negative pressure is formed on the opposite face mainly due to the leading-edge vortices. The positive and negative pressure exchange sides during the switch between the downstroke and the upstroke [41]. A clear illustration of the foil-loading mechanism can be found in the work by Inada et al [68].…”
Section: Propagation and Decay Of Pressure Wavesmentioning
confidence: 93%
“…However, the aeroacoustics induced by the flapping foil has not been well understood [41]. Although the high performance of insect flight can be achieved with low noises, the flapping sound generated by the foil may have potential effects on biological functions, such as the communication using aposematic signals with the locomotion-induced sound [41]. Moreover, the study on the sound induced by flapping foil may also have potential applications in medical inspections, such as the phonation of human which performs like a flapping foil induced sound [4].…”
mentioning
confidence: 99%